The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1002/jcla.24214
|View full text |Cite
|
Sign up to set email alerts
|

MCAM is associated with metastasis and poor prognosis in osteosarcoma by modulating tumor cell migration

Abstract: Background Although there are standard treatment options for osteosarcoma (OS), the prognoses of patients with OS remain varied. Therefore, it is important to profile OS patients at a high risk of mortality to develop focused interventions. Although tumor biomarkers are closely associated with clinical outcomes, data on prognostic biomarkers for OS remain scarce. Methods We collected RNA expression profiles and clinical data of 90 OS patients from the GEO database (dataset GSE21257 and GSE39055) and 96 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
(52 reference statements)
0
5
0
1
Order By: Relevance
“…MCAM was also mentioned to be overexpressed in OS, and its high expression was related to OS metastasis and poor prognosis [27,28]. Overall, the oncogenic effect of MCAM in diverse cancers has been verified.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…MCAM was also mentioned to be overexpressed in OS, and its high expression was related to OS metastasis and poor prognosis [27,28]. Overall, the oncogenic effect of MCAM in diverse cancers has been verified.…”
Section: Discussionmentioning
confidence: 93%
“…MCAM was strikingly elevated in small cell lung cancer with chemoresistance, and the suppression of MCAM largely repressed cancer cell proliferation and drug resistance [ 26 ]. MCAM was also mentioned to be overexpressed in OS, and its high expression was related to OS metastasis and poor prognosis [ 27 , 28 ]. Overall, the oncogenic effect of MCAM in diverse cancers has been verified.…”
Section: Discussionmentioning
confidence: 99%
“…MCAM is highly expressed in various malignancies and has tight association with their growth and metastasis, such as melanoma (46), prostate cancer (47), gastric cancer (48), and lung cancer (49). Prior investigations revealed that MCAM was associated with poor prognosis of osteosarcoma patients and can improve the migration ability of osteosarcoma cells (50). For immunotherapy, MCAM deficiency significantly impairs T cell-mediated antitumor effect (51).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in recently patented data, it has been shown that the placenta, by releasing proangiogenic factors, could constitute a promising source of circulating biomarkers for the early diagnosis of FASD (WO2016207253, Gonzalez et al, 2016 andWO2018100143, Gonzalez et al, 2018). Several recent studies have shown that CD146 has a prognostic biomarker value for the diagnosis of cancer (Lei et al, 2015;Rapanotti et al, 2021;Du et al, 2022). This biomarker potential can be related to the angiogenic properties of CD146 (Joshkon et al, 2020), a physiological function that is dysregulated by PAE (Lecuyer et al, 2017;Léger et al, 2020a).…”
Section: When Altered Angiogenesis Reflects Neurodevelopmental Impair...mentioning
confidence: 99%